Transarterial chemoembolization with or without multikinase inhibitors for patients with unresectable hepatocellular carcinoma: a systematic review and meta-analysis of randomized controlled trials - Dong, Han; Ge, Dongfang; Qu, Biao; Zhu, Ping; Wu, Qibiao; Wang, Tianyun; Wang, Jue; Li, Zheng (Frontiers in Oncology, 2023)
Randomized controlled trials (RCTs) testing the combination therapy of transarterial chemoembolization (TACE) plus multikinase inhibitor (MKI) in patients with unresectable hepatocellular carcinoma (HCC) have yielded inconsistent results. The present study aimed to compare the TACE+MKI combination therapy versus TACE monotherapy in HCC patients by a systematic review and meta-analysis with time to progression (TTP) adopted as primary outcome. A total of 10 RCTs comprising 2837 patients receiving combination therapy (TACE plus sorafenib, brivanib, orantinib or apatinib) were included. TACE+MKI significantly prolonged TTP (hazard ratio [HR] 0.74, 95% CI 0.62-0.89, p=0.001) versus TACE monotherapy. Subgroup analysis suggested MKI administration before TACE might be preferable to post-TACE MKI for TTP. TACE+MKI also increased objective response rate (ORR) (risk ratio [RR] 1.17, 95% CI 1.03-1.32, p=0.01), but failed to improve overall survival (OS) (HR 0.98, 95% CI 0.86-1.13, p=0.82) and progression-free survival (PFS) (HR 0.75, 95% CI 0.50-1.12, p=0.16). The incidence of any adverse event (AE) did not significantly differ between TACE+MKI and TACE groups (RR 1.17, 95% CI 0.96-1.42, p=0.01), while serious AEs showed significant difference (RR 1.41, 95% CI 1.26-1.59, p<0.0001). Nevertheless, these AEs showing significant difference were mainly associated with MKI toxicities rather than TACE. In summary, TACE+MKI combination therapy improved TTP and ORR but not OS and PFS in patients with unresectable HCC. Further high-quality trials are needed to verify these clinical benefits, and our findings could be very informative for future trial design.